Taking Stock of Empowerment Evaluation: An Empirical Review - Miller, Robin Lin; Campbell, Rebecca (American Journal of Evaluation, 2006)
Empowerment evaluation entered the evaluation lexicon in 1993. Since t hat time, it has attracted many adherents, as well as vocal detractors . A prominent issue in the debates on empowerment evaluation concerns the extent to which empowerment evaluation can be readily distinguishe d from other approaches to evaluation that share with it an emphasis o n participatory and collaborative processes, capacity development, and evaluation use. A second issue concerns the extent to which empowerme nt evaluation actually leads to empowered outcomes for those who have participated in the evaluation process and those who are the intended beneficiaries of the social programs that were the objects of evaluati on. The authors systematically examined 47 case examples of empowermen t evaluation published from 1994 through June 2005. The results sugges t wide variation among practitioners in adherence to empowerment evalu ation principles and weak emphasis on the attainment of empowered outc omes for program beneficiaries. Implications for theory and practice a re discussed.